Geographical pattern in the response of the arctic‐alpine Silene suecica (Cariophyllaceae) to the interaction between water availability and photoperiod. Issue 2 (12th December 2014) - Abeli, Thomas; Orsenigo, Simone; Guzzon, Filippo; Faè, Matteo; Balestrazzi, Alma; Carlsson‐Granér, Ulla; Müller, Jonas V.; Mondoni, Andrea
Abstract: We hypothesized a geographical pattern of the plant performance (seedling development, biomass production, relative water content and chlorophyll content) as a result of response to the interaction between photoperiod and water availability in populations of the arctic‐alpine Silene suecica from different latitudes, thus experiencing different photoperiods during the growing season. Particularly, we expected a lower drought sensitivity in northern compared to southern populations as a consequence of harsher conditions experienced by the northern populations in terms of water availability. The experiment was carried out under common garden conditions, manipulating the water availability (wet and dry) and the photoperiod (21 and 16 h). We found an interaction between photoperiod and water availability on plant height, leaves, growth, biomass and total chlorophyll. However, the photoperiod neither counteracted nor intensified the effect of drought. Plants exposed to drought compensated for decreasing water availability by reducing their shoot growth. Changes in the chlorophyll content and chlorophyll a / b ratio were observed. Northern populations showed a higher basal growth performance and a greater response to the changed water regime (from wet to dry) than the southern populations. Southern populations showed a reduced ability to respond to drought, but their low basal performance may be advantageous under low water availability, avoiding water loss. In contrast, northern populations showed a stronger plastic response that limited the negative effects of reduced water availability. This study highlights the possibility that the plant response to environmental constraints (specifically water availability) may follow a geographical pattern.